PENGARUH PEMBERIAN BEBERAPA KONSENTRASI AIR KELAPA TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora) - Eviza, Andi; Azizi, Rahmat; Syariyah, Amaliyah; Amir, Syafri (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
The purpose of this study was to examine the effect of various concentrations of coconut water on the growth of Robusta coffee seedlings and to determine which concentration provided the best effect. This research was conducted at the Payakumbuh State Agricultural Polytechnic, Harau District, Lima Puluh Kota Regency, West Sumatra Province. The research was titled "The Effect of Various Concentrations of Coconut Water on the Growth of Robusta Coffee (Coffea robusta) Seedlings." This study ran for five months, from January 2024 to May 2024. A Completely Randomized Design (CRD) was used, with five treatment levels of varying coconut water concentrations. The five levels were: P0 0% = 2,000 ml water, P1 15% = 300 ml coconut water + 1,700 ml water, P2 30% = 600 ml coconut water + 1,400 ml water, P3 45% = 900 ml coconut water + 1,100 ml water, and P4 60% = 1,200 ml coconut water + 800 ml water, with five replications. The results showed that the effect of various concentrations on coffee seedling growth significantly affected seedling height and diameter, with the best treatment being P3 with a concentration of 45%.